İş Hukukunda Organik Bağ Kavramı - (:unkn) unknown (My University, 2017)
İşverenin de işçi gibi gerçek kişi olduğu iş hukukunun erken döneminde işverenin kim olduğu konusunda belirsizlik yokken, tüzel kişi işverenlerin ön planda olduğu ve şirketlerin gidererek şirket topluluklarına dönüştüğü çağdaş iş hukukunda işverenin kim olduğunun belirlemek pek kolay değildir. İşverenin kimliği konusunda yaşanan karmaşa, işçinin haklarını elde etmesini de güçleştirmektedir. Bu bağlamda, sorun; organik bağ, birlikte istihdam ve tüzel kişilik perdesinin aralanması gibi kavram ve yöntemler kullanılarak çözülebilir. Özellikle işverenler arası organik ba- ğın saptanmasında kullanılacak ölçütlerin tespiti ayrı bir önem taşımaktadır.

While there was no uncertainty during the early period of labor law regarding the identity of the employer who was also a natural person likewise his counterpart employee, it is not always easy to identify the employer at a time during which corporate entities are in question and the companies turn steadily into multi-company entreprises. The confusion concerning the identity of the employer makes it difficult for the employees to obtain their rights. In this context, the problem can be solved through the concepts and methods such as organic tie, joint employment and piercing the corporate veil. Particularly the identification of the criteria with relation to organic tie between employers is of utmost importance.
The Concept of Organic Tie in the Labor Law
Keywords: Hukuk